Lightweight design of semitrailer based on topology optimisation and response surface methodology. (31st January 2022) - Zhou, Shuwen; Xu, Jichao
To improve the fuel economy and transportation efficiency of semitrailers, this paper conducts a lightweight study on semitrailer frame. This paper mainly uses finite element method and combines topology optimisation and response surface method to optimise the suspension and frame. After the optimisation analysis, the best installation size of the suspension is finally obtained, and the weight of the frame is reduced by 507.8 kg to meet the material strength, which achieves a good lightweight effect. The lightweight method of semitrailer proposed in this paper can provide a feasible solution for the lightweight of road transport vehicles.